Flexible Approach for Construction Process Management Under Risk and Uncertainty. (2017) - Paslawski, Jerzy
Abstract: This article presents the basic conditions for the application of a flexible approach to the management of construction processes, resulting primarily from high levels of risk and uncertainty. On the one hand, for simple projects whose implementation is not exposed to dynamically changing environments, the use of flexibility is not justified; on the other hand, in the case of complex, innovative projects implemented in a turbulently variable environment, flexibility gives the opportunity to continue processes despite difficulties. Flexibility can be successfully applied at different levels of management and at different phases of the life cycle of a building. Different flexibility options have been presented based on the approach to real options. A procedure for implementing flexibility in building management was proposed. The flexible approach is illustrated by examples of its use.